Microbiome Modulation—Toward a Better Understanding of Plant Microbiome Response to Microbial Inoculants - Berg, Gabriele; Kusstatscher, Peter; Abdelfattah, Ahmed; Cernava, Tomislav; Smalla, Kornelia (Frontiers in Microbiology, 2021)
Plant-associated microorganisms are involved in important functions related to growth, performance and health of their hosts. Understanding their modes of action is important for the design of promising microbial inoculants for sustainable agriculture. Plant-associated microorganisms are able to interact with their hosts and often exert specific functions towards potential pathogens; the underlying in vitro interactions are well studied. In contrast, in situ effects of inoculants, and especially their impact on the plant indigenous microbiome was mostly neglected so far. Recently, microbiome research has revolutionized our understanding of plants as coevolved holobionts but also of indigenous microbiome-inoculant interactions. Here we disentangle the effects of microbial inoculants on the indigenous plant microbiome and point out the following types of plant microbiome modulations: i) transient microbiome shifts, ii) stabilization or increase of microbial diversity, iii) stabilization or increase of plant microbiome evenness, iv) restoration of a dysbiosis/ compensation or reduction of a pathogen-induced shift, v) targeted shifts towards plant beneficial members of the indigenous microbiota, and vi) suppression of potential pathogens. Therefore, we suggest microbiome modulations as novel and efficient mode of action for microbial inoculants that can also be mediated via the plant.